IMPLEMENTASI PENJUALAN MAKANAN (KULINER) PARA IBU RUMAH TANGGA DIDAERAH KELURAHAN DUA ILIR KECAMATAN ILIR TIMUR II PALEMBANG TANGGA MELALUI MEDIA FACEBOOK - Nozylianty (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
The article entitled Online Culinary Business, Business Solutions in the Middle of the Covid-19 Pandemic discusses the impact of the pandemic on the community's economy, especially in Palembang. Not a few people affected by Covid-19 swerved looking for fortune by selling whatever they could, and the article focused on the culinary business with online marketing. The purpose of this research is to examine the phenomenon of the online culinary business, as a business solution in the midst of the Covid-19 pandemic, especially in Palembang. In this study, literature research is used which in the data collection process directly to the data and by taking various reference sources that support a study. Data collection techniques by interviews, listening to and recording important information. The COVID-19 pandemic has devastated the world economy, especially in Palembang, many people have become victims of this pandemic, but it turns out that there are always positive things behind the disasters that occur. Online culinary business, is a business solution during the Covid-19 pandemic. The culinary business has a promising market sector as a basic human need.